if x = y cos(2π/3) = z cos(4π/3), then xy + yz + zx = ?
Answers
Answered by
6
Answer Let x = y cos 2pie by 3=z cos 4pie by 3 =k Then k/x = 1 ------(a) k/y = cos 2pie by 3 -------(b) k/z = cos 4pie by 3 -------(c)Now by adding (a) , (b) and (c) [k (yz + xz + xy)]/xyz = 1 + cos 2pie by 3 +cos 4pie by 3Taking L.C.M we get k (yz) + k (xz) + k (xy) = 1 + cos 2pie by 3 +cos 4pie by 3Now putting values of (cos 2pie by 3 ) and (cos 4pie by 3) we get[k (yz + xz + xy)]/xyz = 1-(1/2)-(1/2)Then[k (yz + xz + xy)]/xyz = 0k (yz + xz + xy) = 0yz + xz + xy = 0
Answered by
9
please see the attachment
Attachments:
![](https://hi-static.z-dn.net/files/d12/47710c23e38702462a189424b9793a51.jpg)
Anonymous:
please mark brainlist
Similar questions
History,
7 months ago
Math,
1 year ago
Science,
1 year ago
Math,
1 year ago
Political Science,
1 year ago